„Ethnicity, Nationality, Origin of the Nation ...“ - Kadaria, Aza (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
The article „Ethnicity, Nationality, Origin of the Nation ...“ refers to one of Ilia’sletters „Ireland and England - a historical-economic essay“ (Ilia Chavchavadze, Vol. IX, „Letters on Abroad“, p. 9-46; Georgian SSR State Publishing House, Tbilisi, 1957). This extensivestudy was published in the Iverianewspaper in 1886, №№67, 68, 69, 70, 71, 72, 73, 74, 75, 76. Here Chavchavadze discusses Ireland and England and a little bit Scotland as well. Ilia tries to explain the long process of which Ireland faced before it was conquered by Great Britain. Ilia Chavchavadze characterizes traditionally established rules of social behavior of Irish landowners and situation in general after Great Britain took control over Ireland. Ilia’s article clearly shows how England took away the Irish lands handed it over to its nobles. This caused a large emigration of Irishmen abroad to save themselves and their families, while the rest almost starved to death.Mishaps somehow made Irish consolidated and they engaged in battle.They often failed, but they never gave up and continued their fights no matter what. The battle for independence was led by the greatest sons.Progressive part of England was fiercely demanding for changes. The necessity of radical changes towards Ireland was the main call for the government. Parliamentarian Gladstone was one of them, Ilia Chavchavadze especially admired him. In my letter Ilia’s thoughts are briefly described regarding this issue.There is a parallel between situation inGeorgia ( in times of Russian Empire). Here is clearly shown Ilia Chavchavdze’s main thoughts of Georgia in times before becoming a part of Empire and after it. The new rules which came after clearly ruined the plot of independence. The letter emphasizes that all of Ilia’s articles, which were dedicated to the struggle of other nations for independence, served a single purpose: to keep an eye on the society and to show that conscious nations are fighting to restore their supremacy, to regain their own statehood.